HIV/HBV Co-infection - A Global Challenge - Tumpa, Shanjida Islam; Mamun, Abdullah Al (Bangladesh Journal of Medical Science, 2015)
With prevalence worldwide approximately 10% of the HIV-infected population is infected with hepatitis B. In persons with HBV and HIV co-infection, HBV-related liver disease progresses more rapidly than in those with HBV mono-infection leading to increased rates of persistent infection, higher HBV DNA levels, increased cirrhosis and liver-related mortality, increased risk of hepatocellular carcinoma, and decreased efficacy of anti-HBV therapy. Furthermore, HIV-infected patients co-infected with HBV have an increased risk for antiretroviral therapy-related hepatotoxicity. The management of hepatitis B in co-infected patients is complicated because HIV substantially impacts the outcome of HBV. For all of these reasons, effective treatment of HBV in persons co-infected with HIV is clearly high priority. If treatment is indicated in an HBV/HIV co-infected patient, the severity of liver disease, probability of various reactions and potential adverse events should be taken into account. Combination therapy should be used to avoid development of antiviral resistance. Continuous monitoring of HBV patients, the choice of antiviral therapy or history of seroconversion, is vital to recognize reactivation and subsequent need for treatment, to identify drug resistance and viral breakthrough early. Further work is also needed on how to optimize anti-HBV therapy in HIV/HBV co-infected persons and to determine which combinations are most effective and least toxic together with anti-HIV regimens. Little data, however, are available on HIV/HBV co-infection from regions with high chronic hepatitis B prevalence. The authors aim to bring to light the overall status of HIV/HBV co-infection. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.316-322